2003
DOI: 10.1097/01.md.0000076009.64510.b8
|View full text |Cite
|
Sign up to set email alerts
|

Localized Mucosal Leishmaniasis due to Leishmania (Leishmania) infantum

Abstract: The clinical and microbiologic characteristics of 31 patients with mucosal leishmaniasis due to Leishmania (Leishmania) infantum are described. Twenty-eight (90%) patients were male. Mean age at presentation was 48 +/- 14 years. Thirteen (42%) patients had no underlying disease, while 18 (58%) patients had several other medical conditions. Fifteen (48%) patients were immunocompromised, 7 patients were infected with human immunodeficiency virus (HIV), and 3 were graft recipients. The primary location of lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
143
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 48 publications
1
143
0
3
Order By: Relevance
“…However, in the current review (Table 1), we found that leishmaniasis with exclusive primary involvement of the oral mucosa was more frequent in immunocompetent patients (14 cases, 70.0 %). In immunocompromised patients, we found 6 cases (31.6 %), with 3 (15.8 %) in HIV-positive patients [3,6] and diabetes, kidney transplant, and corticotherapy with one case each [5][6][7]. Interestingly, in all cases that were difficult to diagnosis, the patients were HIV-negative, whereas in HIVpositive patients the parasite was easily visualized in the tissues.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, in the current review (Table 1), we found that leishmaniasis with exclusive primary involvement of the oral mucosa was more frequent in immunocompetent patients (14 cases, 70.0 %). In immunocompromised patients, we found 6 cases (31.6 %), with 3 (15.8 %) in HIV-positive patients [3,6] and diabetes, kidney transplant, and corticotherapy with one case each [5][6][7]. Interestingly, in all cases that were difficult to diagnosis, the patients were HIV-negative, whereas in HIVpositive patients the parasite was easily visualized in the tissues.…”
Section: Discussionmentioning
confidence: 87%
“…We found only 19 cases of leishmaniasis, with involvement reported exclusively in the oral area in the English-language literature [3][4][5][6][7][8][9][10][11][12][13], and 6 cases in immunocompromised patients [3,[5][6][7]. These lesions usually appear as erythema and ulceration or as plaque, papules, and/or exophytic nodules, usually affecting the hard or soft palate and tongue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Los hallazgos endoscópicos de la leishmaniasis laríngea incluyen ulceración transglótica bilateral, edema perilesional, 3 hipertrofia de bandas ventriculares, 1,14 masas exofíticas de apariencia granular, 14 vegetación ulcerada y granulomas en cuerdas vocales. 5,14 En nuestro paciente, se encontró hipertrofia de la epiglotis y edema glótico y ocupación de la vallécula.…”
Section: Discussionunclassified
“…5,6 Se han documentado casos secundarios a la reactivación de la forma visceral por Leishmania donovani e infantum. 7 Hasta el 3% de las formas cutáneas por Leishmania braziliensis afectan las mucosas concomitantemente o después de 2 años de la remisión, como resultado de la diseminación linfohematógena del parásito.…”
Section: Nasolaryngotracheal Mucosal Leishmaniasis In An Adolescentunclassified